Pelatihan Pengisian E-faktur pada PKP di Kota Lamongan - Umar Yeni Suyanto; Sri Yaumi; Amanatul Khoiriyyah (BADAN PENERBIT STIEPARI PRESS, 2021)
Electronic tax invoices or E-faktur were introduced in 2013 with the provisions stipulated in the Regulation of the Director General of Taxes. Provisions for changes in making electronic tax invoices were amended several times until the issuance of PER-16/PJ/2014 Article 1 paragraph (1) which requires certain PKPs to make e-invoices. The perceived benefits for PKP are the convenience of entrepreneurs and protection from misuse by irresponsible parties. In addition, for the Directorate General of Taxes, E-faktur facilitates supervision and facilitates service. With so many PKPs who do not understand and have competence in filling out E-invoices, the Institut Teknologi dan Bisnis Ahmad Dahlan Lamongan community service team provides training in filling in E-invoice 3.0 for PKPs. The results of this community service have an impact on increasing the knowledge and skills of participants in the field of taxation, especially related to E-Faktur.